Dance for Health: The perceptions of healthcare professionals of the impact of music and movement sessions for older people in acute hospital settings. (13th September 2020) - Bungay, Hilary; Jacobs, Clare
Abstract: Aim and objectives: To explore staff perceptions of the impact of weekly music and movement sessions involving older patients and staff on the wards where 'Dance for Health' sessions take place. Background: Dance for Health is a programme of weekly group dance sessions, which take place on wards in an acute hospital setting. Recent research demonstrates the value of creative arts activities in clinical settings across the globe. However, there is little research exploring the impact of dance programmes for frail older people in acute hospital settings, or healthcare professionals' perceptions of the impact of these sessions on patients, staff and the ward environment. Method: A qualitative descriptive approach was used. Twenty‐one semi‐structured interviews were conducted with staff who had supported patients participating in Dance for Health and the ward managers where the sessions took place. Data analysis was undertaken using a thematic analysis approach. Findings: The sessions challenged staff assumptions about older patients' musical preferences and the level of physical activity patients were able to undertake. Staff felt that the shared experience and interactions within the group enhanced staff–patient relationships. Staff taking part in the sessions reported feeling pleasure seeing their patients enjoying themselves and valued being a part of delivering the sessions. Conclusion: The Dance for Health programme in an acute hospital setting has the potential to promote person‐centred care through encouraging self‐expression and individuality. It is a meaningful and enjoyable activity, which encourages physical activity and social interaction and enriches the aesthetic experience of the hospital environment. Implications for practice: This is the first study reporting on the use of dance sessions for older people in an acute hospital setting. Dance for Health had a positive impact on staff attending the sessions and enhanced staff–patient relationships. Staff support is key for effective delivery.